Early Permian to Middle Triassic Formation petroleum potentials of Sydney Basin, Australia: A geochemical analysis - Garba Terfa Elijah; Mustapha Khairul Azlan; Asiwaju Lanre; Mutari Lawal (Open Geosciences)
The organic geochemical and petrological analyses of calculated vitrinite reflectance of the Early Permian to Middle Triassic Formation section of the Sydney Basin in Australia have revealed the source for the widely distributed oil and gas shows in the basin. The coal formations of the Permian in the Sydney Basin have a higher hydrogen index with much higher TOC extracts than the non-coal formations of the Permian in the same basin. Some source-specific parameters attained from biomarkers, such as n-alkanes, regular isoprenoids, terpanes, diasteranes, and steranes, show that oil was generated and expelled mainly from organic matter derivatives of higher plants deposited in the oxic environment. The biomarkers associated with maturity, source, and aromatic hydrocarbon are mostly from coal core samples. However, extracts from non-coal samples have an organic geochemical signature, indicative of mixed terrestrial and prokaryotic organic matter deposited in a suboxic environment. Significantly, it is different from the coal extracts. Still, the molecular signature of some of the coal samples shows prokaryotic organic matter present in the extracts, indicating a thin section of possibly a calcareous lithology interbedded within the coal measure formation. Genetically, the coal extracts of the Permian in the Sydney Basin, Australia, provide a new insight into the generation and expulsion of oil from coal, which might be responsible for the widespread oil and gas shows in the basin. This raises the possibility of commercial oil accumulation in the early Permian coals to Middle Triassic sandstones, perhaps in the deeper part of the offshore basin.